1996
DOI: 10.1093/infdis/174.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Immunogenicity, and Efficacy of Plasmodium falciparum Repeatless Circumsporozoite Protein Vaccine Encapsulated in Liposomes

Abstract: Seventeen malaria-naive volunteers received a recombinant Plasmodium falciparum vaccine (RLF) containing the carboxy- and the amino-terminal of the circumsporozoite protein (CSP) antigen without the central tetrapeptide repeats. The vaccine was formulated in liposomes with either a low or high dose of 3-deacylated monophosphoryl lipid A (MPL) and administered with alum by intramuscular injection. Both formulations were well tolerated and immunogenic. MPL increased sporozoite antibody titers measured by ELISA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 35 publications
1
49
0
1
Order By: Relevance
“…The active ingredients of both adjuvants are 3-deacylated MPL (3D-MPL) (35)(36)(37)(38), a nontoxic derivative of LPS and QS21 (a triterpene glycoside purified from the bark of Quillaja saponaria, (39 -41), and both components have a good clinical safety record (31,32,42,43). The biological properties of MPL are attributed to its immunostimulatory effects on the innate immune system (via activation of the Toll-like receptor 4) and the direct activation of APCs resulting in enhanced phagocytosis and microbicidal activities as a consequence of the production of IL-12, TNF-␣, GM-CSF, and IFN-␥ (36,38,44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active ingredients of both adjuvants are 3-deacylated MPL (3D-MPL) (35)(36)(37)(38), a nontoxic derivative of LPS and QS21 (a triterpene glycoside purified from the bark of Quillaja saponaria, (39 -41), and both components have a good clinical safety record (31,32,42,43). The biological properties of MPL are attributed to its immunostimulatory effects on the innate immune system (via activation of the Toll-like receptor 4) and the direct activation of APCs resulting in enhanced phagocytosis and microbicidal activities as a consequence of the production of IL-12, TNF-␣, GM-CSF, and IFN-␥ (36,38,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The distinction between AS01B and AS02A formulations resides in their liposome or oilin-water emulsion properties, respectively. Both adjuvants as well as their components are currently under clinical evaluation for various vaccines and has been tested in thousands of patients in several clinical trials, including infectious disease vaccines such as malaria (31,33), hepatitis B (50, 51), and allergy desensitization (52)(53)(54). Furthermore, the use of MPL-stable emulsion as an alternate adjuvant to IL-12, known for its Th1-inducing properties, in conjunction with a polyprotein Ag was recently demonstrated as a safe and effective vaccine against Leishmania infection (55).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the adjuvants tested in the current study was based on reports of the literature indicating that they have been previously shown to work in anti-leishmania vaccine experiments and that they were commercially available and licensed to be used in humans and/or animals. Both AdjuPrime ® and MPL-SE ® fulfill these criteria [10,21,22,42,43]. Immunogenicity of the recombinant antigens was measured primarily by ELISA specifically designed to detect canine antibodies of IgG isotypes specific for the recombinant antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study we observed that RTS,S/MPL/Alum or RTS,S/ AS04 could induce a CS protein peptide-specific CD8 ϩ CTL response (29). Moreover, we previously demonstrated that inclusion of CS protein in liposomes allows MHC class I presentation of CS to CD8 ϩ T cells in mice (30) and to a less detectable degree in humans (31). We speculate, therefore, that AS02A enhanced RTS,S entry into the cytosol of an APC for the generation of CS protein peptide-specific CD8 ϩ T cells.…”
Section: Cd4 ϩ and Cd8 ϩ T Cells Produce Ifn-␥mentioning
confidence: 97%